Krisis Kepercayaan Indeks Global: Analisis Hukum atas Eksklusi Saham Indonesia dari MSCI 2026 dan Implikasinya terhadap Perlindungan Investor Ritel serta Ekosistem Startup Digital - Mochamad Raka Putra Soebandono (CV. ITTC INDONESIA, 2026)
The exclusion of 18 Indonesian stocks from the MSCI index in May 2026 represents a landmark event that exposed structural gaps in Indonesia's capital market regulations, particularly regarding shareholding transparency and retail investor protection. This study aims to analyze Indonesia's legal framework in responding to the MSCI 2026 exclusion, identify gaps in legal protection for retail investors harmed by massive forced selling by foreign institutional investors, and examine the implications of the exclusion for Indonesia's growing digital startup ecosystem. This research employs a normative juridical method with statutory and conceptual approaches, referencing Law No. 8 of 1995 on Capital Markets, the Financial Sector Development and Strengthening Law, and relevant OJK regulations. The findings indicate that the MSCI 2026 exclusion stemmed from inadequate disclosure mechanisms for highly concentrated shareholding structures. Reforms implemented by OJK and BEI in April 2026 have not fully addressed retail investor protection gaps, particularly due to the absence of compensation mechanisms for losses resulting from forced selling. Furthermore, the resulting negative market sentiment has adversely affected pre-IPO digital startup valuations and weakened investor confidence in Indonesia's Securities Crowdfunding platforms.